Improving efficiency in the MSW collection and disposal service combining price cap and yardstick regulation: The Italian case - Giacomo Di Foggia; Massimo Beccarello (Waste Management, 2018)
The municipal solid waste collection and disposal service is a key element of the European strategy aimed at moving towards a circular economy. An efficient municipal solid waste collection and disposal is closely related to both lower waste tax and higher welfare of the interested population. In Italy, the lack of a centralized regulatory framework has determined heterogeneous performances of sector operators across the country. Firstly, we will be estimating the productive efficiency in different optimal territorial areas and secondly we will be forecasting the economic benefits that would arise under a new regulatory regime. Our approach combines the well-known yardstick competition and the price-cap mechanisms. Results suggest that if all territorial areas converged to the most efficient ones, a potential saving between 12% and 19% emerges, i.e., up to exteuro2bn savings out of exteuro10.05bn total tax revenue in 2015.
Keywords: Q53; 330; waste tax; yardstick competition; MSW; price cap; waste management; Efficiency